A design model for knowledge-based pricing services in the retail industry. (1st January 2011) - Kowatsch, Tobias; Maass, Wolfgang
Marketing research has identified several benefits of dynamic pricing strategies in the retail industry. However, today's retailers are limited to apply them in real-time to customer needs as corresponding pricing services provided by smart product infrastructures have not been adopted so far. In addition, dynamic pricing strategies rely on a business service ecosystem of retailers, suppliers, customers and regulatory bodies and thus, interoperability is required. Because unprecedented, our objectives are therefore to propose, implement and evaluate a design model for pricing services that rely on explicit semantics and rules, denoted as knowledge-based pricing services (KPSs). In this work, we propose a design model for KPSs and empirically evaluate their utility from a customer perspective with the help of a web-based application. We finally draw implications for business models in the retail industry and discuss tools that already exist to adopt KPSs in the near future.